A UFLC/MS/MS method for simultaneous quantitation of alisol A and alisol B 23-acetate from Alisma orientale (Sam.) Juz. in rat plasma - Yaowen Zhang; Qing Li; Chunxiao Lv; Yidi Yin; Kaishun Bi (Elsevier, 2014)
A sensitive and reliable ultra fast liquid chromatography tandem mass spectrometry (UFLC-MS/MS) method has been developed and validated for simultaneous quantitation of alisol A and alisol B 23-acetate from Alisma orientale (Sam.) Juz. in rat plasma using diazepam as an internal standard (IS). The plasma samples were extracted by liquid-liquid extraction with methyl tert-butyl ether and separated on a Venusil MP C18 column (100 mm × 2.1 mm, 3.0 mm) (Venusil, China) using gradient elution with the mobile phase consisting of methanol and 0.1% acetic acid in water at a flow rate of 0.4 ml/min. The two analytes were monitored with positive electrospray ionization by multiple reaction monitoring mode (MRM). The lower limit of quantitation was 5.00 ng/ml for alisol A and 5.00 ng/ml for alisol B 23-acetate. The calibration curves were linear in the range of 5.00-2500 ng/ml for alisol A and 5-2500 ng/ml for alisol B 23-acetate. The mean extraction recoveries were above 63.8% for alisol A and 68.0% for alisol B 23-acetate from biological matrixes. Both intra-day and inter-day precision and accuracy of analytes were well within acceptance criteria (15%). The validated method was successfully applied to the pharmacokinetic study of alisol A and alisol B 23-acetate in rat plasma after oral administration of alcohol extract of Alismatis Rhizoma.